(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The derivatives market plays a crucial role in the Indian economy. Financial instrument,indicator, or commodity-specific instruction for the purpose of risk management in the financial markets.The Indian derivatives industry is worth several trillion dollars and is quickly developing. Examples ofDerivative Instruments include those based on commodities, precious metals, foreign exchange rates,bonds, shares and share warrants, short-term securities, and money market products. Both the NationalStock Exchange (NSE) and the Bombay Stock Exchange are major participants in India’s derivativesmarket (BSE). Potential topics include the popularity of derivatives in the Indian economy. In this paperdiscuss the difficulties encountered by the derivatives industry, the market’s worth, and the significance ofits future prospects in the current investigation.